Dietary iodine intake, therapy with radioiodine, and anaplastic thyroid carcinoma - Bešić, Nikola (Radiology and oncology (Ljubljana), 2020)
Anaplastic thyroid cancer (ATC) is one of the most aggressive tumors. The aim of the study was to determine the correlation between a higher dietary intake of iodine, frequency of ATC and the characteristics of ATC, and to find out how often patients with ATC had a history of radioiodine (RAI) therapy. Patients and methods. This retrospective study included 220 patients (152 females, 68 males; mean age 68 years) with ATC who were treated in our country from 1972 to 2017. The salt was iodinated with 10 mg of potassium iodide/ kg before 1999, and with 25 mg of potassium iodide/kg thereafter. The patients were assorted into 15-year periods: 1972%1986, 1987%2001, and 2002%2017. Results. The incidence of ATC decreased after a higher iodination of salt (p = 0.04). Patients are nowadays older (p = 0.013) and have less frequent lymph node metastases (p = 0.012). The frequency of distant metastases did not change over time. The median survival of patients in the first, second, and third periods was 3, 4, and 3 months, respectively (p < 0.05). The history of RAI therapy was present in 7.7% of patients. Conclusions. The number of patients with a history of RAI therapy did not change statistically over time. The incidence of ATC in Slovenia decreased probably because of higher salt iodination.
Keywords: anaplastični rak; jod; jodiranje; preživetje; ščitnica